Fabrication and testing of sustainable bioinspired elephant skin mycelium tiles for the built environment - Martono, Riasa Fadhilla (Nanyang Technological University, 2024)
In response to the pressing challenges posed by carbon emissions from mechanical cooling systems and the use of unsustainable building materials, there is an urgent need for innovative solutions that prioritize environmental sustainability. The development of elephant skin mycelium tiles emerges as a particularly promising avenue to solve the problem. These tiles offer a natural, sustainable, and bioinspired alternative for the built environment, harnessing the unique properties of mycelium to address environmental concerns. This research delves into their feasibility primarily focusing on their thermal properties for potential application as building façades, particularly within Singapore’s urban environment. Through a comprehensive series of experiments and analyses, the study evaluates the potential of these bioinspired tiles in reducing environmental impact and decreasing dependency on mechanical cooling systems in a building. Key areas of exploration include comparative analyses of two different elephant skin designs, assessment of indoor dry and wet performance, and outdoor performance tests. The findings highlight promising results on the heat dissipation capabilities of elephant skin mycelium tiles, indicating their potential significance for sustainable design practices across environmental contexts. By identifying limitations and suggesting avenues for future research, this study contributes to advancing sustainable building practices and highlights the transformative potential of mycelium-based solutions in fostering a more sustainable future.